Review of the methodology of lower limb prosthesis - Zaborna, Daria; Szmelcer, Beniamin; Krakowska, Natalia; Fortuna, Aleksandra; Wszelaki, Patrycja; Florczak, Aleksander; Wilczyński, Michał; Gajos, Małgorzata; Skierkowska, Natalia; Porada, Mateusz; Wąsicki, Mariusz; Modrzejewski, Mateusz; et al. (Journal of Education, Health and Sport, 2019)
Background: The replacement of inefficient or lost organs, especially in the case of lower ends, is associated with a huge experience for the patient, especially in emotional terms. However, with the development of medicine and technology, they allow patients, with properly conducted rehabilitation, to achieve satisfaction with the obtained effects of the treatment. The variety of forms of lower limb prosthesis depends primarily on the location of the prosthesis.Material and methods: Analysis of available literature, articles in the Google Scholar and PubMed database using keywords: Prosthesis, Lower limb, AmputationResults: The lower limb prosthesis is built from a funnel that matches the stump, the mechanism of the knee joint, shin and the foot. Pours that are used at the lower extremities include: a quadrangular funnel, an ICS longitudinal oval or a CAD-CAM, a full-contact hip funnel, a residual femoral funnel or vacuum syphilis used in people with neoplastic amputations. In the case of knee joints, the distinction is made based on the number of axes around which the movement takes place. So we distinguish uniaxial and multi-axis joints. As important as the other parts is the construction of the prosthetic foot, because it is responsible for supporting the limb stabilizers through passive control of the ankle bending.Conclusions: With the new generation of lower limbs prostheses, the patient can lead an active professional life, as well as practice various sports disciplines. However, this does not change the fact that there is still a great need for research, and holistic cooperation to increase the efficiency and satisfaction of life of amputees in the lower limbs.